Psychodemographic Factors Influencing Social Wellbeing among Mobile Police Force in Kwara State, Nigeria - Oguntayo, Rotimi; Abayomi, Olaseni; Helen, Osinowo; Tunde, Oyeleke, Johnson (My University, 2020)
Introduction: There is overwhelming evidence on the increase of dysfunctional social wellbeing among service members returning from deployment, and this is culminating into wide range of social challenges. The study investigated psycho-demographic factors influencing social wellbeing among mobile police force in Kwara State, Nigeria.. Method: The study adopted a survey method utilizing an ex-post-facto design; purposive sampling technique was used to sample 200 mobile police officers (152 males and 48 females). They completed a questionnaire pack which included-the Post-Deployment Readjustment Inventory Scale, Emotion Regulation Questionnaire and Mental Health Continuum of Social Wellbeing-Short Form. Data were analysed using descriptive statistics, Pearson Product Moment Correlation, ANOVA and Multiple Regression. Results: Findings showed that emotion regulation has positive relationship with social wellbeing. Also, age, emotion regulations and post-deployment stress as a whole did significantly predict social wellbeing among the sampled participants. However, emotion regulation did independently predict social wellbeing, though marital status did not significantly influence social wellbeing among the participants. Conclusion: The study present emotion regulation as a great predictor of social wellbeing. It is recommended that; emotion regulation should be built into the training and debriefing of mobile police before and after deployment to aid their better social wellbeing.ls.
Keywords: Age; Emotion Regulation; Police; Post-deployment stress; Social Wellbeing